The Effect of Balloon Rocket Play Therapy on Anxiety in Preschool Children During Hospitalization - Bulan Rexy Pratiwi; Siti Arifah (GLOBAL HEALTH SCIENCE GROUP, 2025)
Preschool children aged 3-6 years are affected exposure environment new when treated At home Sick will result emergence feeling anxious and afraid. One of effort For reduce worried that is with give therapy play balloon rockets. Objective: This study was conducted using the T test which showed the effect of Rocket Balloon Play Therapy on Anxiety in Preschool Children Due to Hospitalization. The P value is <0.001 which means it is less than 0.05 (0.001 <0.05). Method: This study is a quasi-experimental study with a one group pretest-posttest design and uses a purposive sampling technique with a sample size of 20 children. Result: This study was conducted using the T test which showed the effect of Balloon Rocket Play Therapy on Anxiety in Preschool Children Due to Hospitalization. The P value is <0.001, which means it is less than 0.05 (0.001 <0.05). Conclusions: There is an effect of balloon rocket play therapy on preschool children's anxiety during hospitalization in the children's ward of UNS Sukoharjo Hospital.